Is momentum trading profitable from Shari'ah compliant stocks?. Issue 1 (19th August 2016) - Li, Bob; Ee, Mong Shan; Rashid, Mamunur
Abstract: This research offers fresh evidence supporting the pervasiveness of the momentum effect. Two decades after the momentum profitability firstly documented by Jegadeesh and Titman (1993), yet little research has been specifically devised for the momentum profitability on Shari'ah compliant stocks. We assess the momentum profitability over the Shari'ah compliant stocks in a Malaysian setting. We find evidence of strong return persistence as far as toward four‐year holding period. Interestingly, no significant momentum returns are found among the conventional stocks. Upon further exploration we find neither an industry‐driven momentum effect nor the small size firms can account for the momentum returns. Using return persistency formation criteria, we further find that underreaction seems to well fit in explaining this unique long lasting momentum profitability.